1982
DOI: 10.1099/0022-1317-58-2-305
|View full text |Cite
|
Sign up to set email alerts
|

Are 'Pathogenesis-related' Proteins Involved in Acquired Systemic Resistance of Tobacco Plants to Tobacco Mosaic Virus?

Abstract: SUMMARYFour host-coded 'pathogenesis-related' proteins accumulate systemically in locallesion-forming varieties of tobacco after infection with tobacco mosaic virus. It has been suggested that they are involved in the acquired systemic resistance of plants to a second inoculation. Pathogenesis-related protein concentration and amount of resistance (reduction in size and number of lesions formed in the second inoculation) were measured at various times after the first inoculation. The results showed no quantita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
1
1

Year Published

1985
1985
2012
2012

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(34 citation statements)
references
References 26 publications
4
28
1
1
Order By: Relevance
“…In tomato, high ABA levels are predominantly associated with high susceptibility but, in Arabidopsis, both positive and negative effects have been reported (Asselbergh et al 2008a). It is known that TMV infection is able to increase ABA concentration in tobacco (Fraser 1982;Whenham et al 1986) and that infecting bacteria enhance ABA levels in early stages of interaction in order to promote plant infection (Maksimov 2009). Mutants unable to synthesize ABA show enhanced resistance to several biotrophic and necrotrophic fungi (Maksimov 2009;Mauch-Mani and Mauch 2005).…”
Section: Abamentioning
confidence: 99%
“…In tomato, high ABA levels are predominantly associated with high susceptibility but, in Arabidopsis, both positive and negative effects have been reported (Asselbergh et al 2008a). It is known that TMV infection is able to increase ABA concentration in tobacco (Fraser 1982;Whenham et al 1986) and that infecting bacteria enhance ABA levels in early stages of interaction in order to promote plant infection (Maksimov 2009). Mutants unable to synthesize ABA show enhanced resistance to several biotrophic and necrotrophic fungi (Maksimov 2009;Mauch-Mani and Mauch 2005).…”
Section: Abamentioning
confidence: 99%
“…Fraser found that treatment with ABA causes a 70% reduction in lesion number [17]. Treatment of barley roots with ABA activated resistance in response to Blumeria graminis f. sp.…”
Section: Introductionmentioning
confidence: 99%
“…Compounds known to enhance resistance to viruses in animal systems, such as 2-thiouracil and dioxohydrotriazine, were found to induce PRS in plants (White et al, 1986). Methylbenzimidazol-2-yl-carbonate, which has cytokinin-like properties (Fraser, 1982), and a number of amino acids and their analogues (Asselin, et al,.1985) exhibited some degree of PR gene induction, as did several metal ions such as silver, cadmium, manganese, and barium (Asselin et al,1985;White et al, 1986). Two compounds associated with phosphatidylinositol metabolism, phytic acid (Maiss and Poehling, 1983) and arachidonic acid (Malamy et al, 1991) also stimulate PR gene expression.…”
Section: Chemical Inducers Several Chemicals Have Been Shown To Indumentioning
confidence: 99%